Effectiveness of Drug-Eluting Stents versus Bare-Metal Stents in Large Coronary Arteries in Patients with Acute Myocardial Infarction - Sim, Doo Sun; Jeong, Myung Ho; Ahn, Youngkeun; Kim, Young Jo; Chae, Shung Chull; Hong, Taek Jong; Seong, In Whan; Chae, Jei Keon; Kim, Chong Jin; Cho, Myeong Chan; Seung, Ki Bae; Park, Seung Jung (Journal of Korean medical science, 2011)
This study compared clinical outcomes of drug-eluting stents (DES) versus bare-metal stents (BMS) in large coronary arteries in patients with acute myocardial infarction (MI). A total of 985 patients who underwent single-vessel percutaneous coronary intervention (PCI) in large coronary arteries (≥ 3.5 mm) in lesions < 25 mm were divided into DES group (n = 841) and BMS group (n = 144). Clinical outcomes during 12 months were compared. In-hospital outcome was similar between the groups. At six months, death/MI rate was not different. However, DES group had significantly lower rates of target-lesion revascularization (TLR) (1.7% vs 5.6%, P = 0.021), target-vessel revascularization (TVR) (2.2% vs 5.6%, P = 0.032), and total major adverse cardiac events (MACE) (3.4% vs 11.9%, P = 0.025). At 12 months, the rates of TLR and TVR remained lower in the DES group (2.5% vs 5.9%, P = 0.032 and 5.9% vs 3.1%, P = 0.041), but the rates of death/MI and total MACE were not statistically different. The use of DES in large vessels in the setting of acute MI is associated with lower need for repeat revascularization compared to BMS without compromising the overall safety over the course of one-year follow-up.